Difficulties in reading and writing in the English language among first-grade intermediate students from their teachers’ point of view and ways to Overcome - Hammood Shbaki, Assist . Lect. Fadhil (Basra studies journal, 2023)
The current research aims to identify: Reading and writing difficulties in English language among first intermediate grade students from the point of view of their teachers. And figure out if there are any differences among genders and years of service. To achieve the objectives of the research, the researcher prepared a reading and writing difficulties scale that was subjected to statistical analysis, and psychometric properties were extracted from validity and reliability. The results showed that the difficulty of writing is prevalent in the current research sample, where the arithmetic mean value of the difficulty of writing was the highest value (68.15) and the lowest value is the difficulty of reading (66.02).